STUDI PUSTAKA TENTANG HUBUNGAN TINGKAT KECUKUPAN GIZI DAN SIKLUS MENSTRUASI DENGAN ANEMIA PADA REMAJA PUTRI DI BEBERAPA WILAYAH DI INDONESIA TAHUN 2021 - Delvira Auriani Fauziah; Hernowo Anggoro Wasono; Devita Febriani Putri; Ismalia Husna (Medula, 2022)
Nutritional problems in Indonesia include two things, namely excess nutrition and undernutrition. Anemia is a condition in which the hemoglobin level is very low compared to normal. Menstruation is one of the biological signs, which is related to the achievement of sexual maturity, fertility, body health, and even changes in some forms of the body itself. Adolescence is a period where the growth process occurs in a very short time. Aim for knowing the relationship between the level of nutritional adequacy and the menstrual cycle with anemia in adolescent girls in several regions in Indonesia in 2021. This study is a descriptive study using a literature study design using the Google Scholar search engine with the research population namely young women and the research sample being young women which is the subject of 8 journals studied. Of the 8 journals that have been studied with the results of a relationship between the level of nutritional adequacy and anemia with p = value (<0.5) and there is no relationship between menstrual cycle and anemia with p=value (>0.5). There is a significant relationship between the level of nutritional adequacy with anemia and there is no significant relationship between the menstrual cycle and anemia.